"The Promotora Explained Everything": Participant Experiences During a Household-Level Diabetes Education Program. (July 2014) - Shepherd-Banigan, Megan; Hohl, Sarah D.; Vaughan, Catalina; Ibarra, Genoveva; Carosso, Elizabeth; Thompson, Beti
Purpose: The purpose of this study is to describe participant experiences of a household-level, community health worker-led intervention to improve diabetes-related health behaviors and outcomes. Methods: The Home Health Parties (HHP) aimed to improve diabetes self-management among Hispanics living in a rural, agricultural area in eastern Washington State. Trained promotores (community health workers) delivered a series of education sessions and distributed incentives to support diabetes-related behavior change. Open-ended, semi-structured questionnaires were administered to a random sample of 40 HHP participants. Qualitative methods were used to code and analyze the interview transcripts. Results: Four primary themes emerged from interviews: (1) participants' desire for improving knowledge about diabetes; (2) experiences of building skills for diabetes management; (3) developing social support; and (4) embracing household-level change. Conclusion: This study shows that involving family members and increasing social support are effective strategies for improving health behaviors and chronic health outcomes among vulnerable Hispanics living with diabetes. Our findings demonstrate several important considerations regarding the design of diabetes management interventions for rural Hispanic populations including the following: (1) promotores are critical as they provide social support and encourage behavior change by building relationships based on trust and cultural understanding; (2) well-designed tools that provide step-by-step examples of healthy behaviors, such as cookbooks, and tools that aid participants to monitor behavior change, such as pedometers and glucose monitors, serve to build skills and improve confidence to achieve goals; and (3) targeting households is a promising strategy for individual and family lifestyle changes that benefit the entire family unit.